366 MEDIAL MALLEOLAR STRESS FRACTURE IN AN INTERCOLLEGIATE FOOTBALL PLAYER. (1st January 2005) - Moazzaz, P.; Chang, C. J.
Abstract : Stress fractures of the medial malleolus are rare injuries associated with substantial morbidity. These debilitating fractures represent a diagnostic challenge, as they are often mistaken for ligamentous or syndesmotic injuries. The proper management of medial malleolar stress fractures is also unclear, however there is a substantial body of literature describing the need for open reduction and internal fixation using cancellous screws in elite athletes. We report a case of a 20-year-old Division I football player sustaining a medial malleolar stress fracture that was successfully treated nonoperatively with no time missed from games. Case: B.H., a 20-year-old Division I Football tight end was attempting to block another player when he sustained a forced hyper-dorsiflexion injury to his right ankle. He could not sprint for the remainder of practice and any attempt to push off was also painful. On clinical exam, he demonstrated 5/5 strength and full range of motion with pain at full passive dorsiflexion. He did not demonstrate a joint effusion and was negative for talar tilt, anterior drawer, and squeeze tests. Radiographs taken the next morning were negative, however one month later he was seen by team physicians for persistent anterior ankle pain during running activities and during squats in the weight room. Repeat right ankle radiographs were significant for a subtle linear lucency of the medial distal tibia, and MRI demonstrated diffuse marrow edema extending through the medial tibial plafond with a partial tear of the tibiocalcaneal component of the deltoid ligament. CT scans confirmed a fracture of the anterior cortex of the medial distal tibia. The athlete was restricted to a walking boot for all activities of daily living and practices were modified to limit impact loading and sprinting. He was placed on a bone stimulator for four weeks and received rehabilitation including strengthening, proprioceptive work, and lower extremity stretching. He began to improve over the next several weeks and was able to participate fully on game-days throughout his injury. He was followed with serial radiographs. At the end of the season, (8 weeks s/p injury) he was placed in a fiberglass cast and non-weightbearing on crutches. Twelve days later the cast was removed and he was then placed in a walking boot. Follow-up CT scan at this time revealed progressive healing. As he was asymptomatic, he was weaned from the walking boot and is now participating fully in spring football.